English for spesific purposes (Graha Ilmu, 2015)
This book is designed for teachers, trainers, course organizers who work in the field of English for specific purposes (ESP). It gives the relevant background to the ESP learners' world, and then presents strategies for teachers approaching the training tasks. In particular, the author presents an approach which focuses on the learners' professional knowledge and experience.